The correlation between family role and anemia prevention in pregnancy - Mira Triharini; Ni Ketut Alit Armini; Sekar Ayu Pitaloka (PAGEPress Publications, 2023)
Introduction: It is important to reduce the high incidence of anemia in pregnancy globally. Pregnant women need the support of their families to face any difficulties in order to prevent anemia. Design and Methods: This study aims to determine the correlation between family role and anemia prevention in pregnancy. This cross-sectional study was conducted in August 2021 among 60 pregnant women who went for check-ups at two primary healthcare centers in Surabaya, Indonesia, and received iron supplements. Additionally, it was discovered that family role andanemia prevention in pregnancy were evaluated using questionnaires. Result: The Spearman test was used as a test for significance and the results showed that there was a correlation between family role and anemia prevention in pregnancy (r = 0.318; P = 0.013). Also, it was found that informational, emotional, and affirmational support, as well as having a role model were significantly correlated with anemia prevention at (r = 0.311; p = 0.015), (r = 0.265; p = 0.041), (r = 0.400; p = 0.002), and (r = 0.353; p = 0.006), respectively. Conclusions: There was a relationship between family role and anemia prevention in pregnancy, as well as adequate nutrition, adherence to iron supplements, and prevention of worms. Therefore, there is the need for health promotion to the families of pregnant women in order to increase the understanding of anemia prevention in pregnancy.